Critical Land Conservation to Save Biodiversity, Case Study: Organic Forest, Megamendung, Bogor, Indonesia - Afrianda, Rio; Yasin, Tania Revina (Technium Social Sciences Journal, 2023)
The Muara Karang steam power plant is one of the power plants in Indonesia which is managed by PT PLN Nusantara Power as a state-owned company. In carrying out its business, it has potential impacts on the environment, one of which is on biodiversity. The aim of this research is to analyze the potential of biodiversity resources by conserving critical land in the Organic Forest, Megamendung, Bogor, Indonesia. The method used is a natural forest model scenario including organic farming, reforestation, and sustainable organic farming in a natural rehabilitation process. Rehabilitation is carried out using an agroforestry system, intercropping between forestry and agricultural crops, and fertilization using manure. This planting was carried out by the community as a form of empowerment which succeeded in creating jobs as farmers and participating in managing the forest. As a start, 3,000 tree seeds and intercrops such as edamame, corn, cassava, and taro have been planted. The results of this research in monitoring in 2022, the proportion of tree habitat increased from 40% to 54%, the diversity index (H') of birds increased from 2.17 to 3.22, H' of mammals from 1.76 to 2.05, H' of herpetofauna from 2.08 to 2.82, and H' of arthropods from 3.73 to 3.87.